2021
DOI: 10.1002/rmv.2241
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent viral tropism: understanding viral seasonality and pathogenicity as applied to the avoidance and treatment of endemic viral respiratory illnesses

Abstract: Summary This review seeks to explain three features of viral respiratory illnesses that have perplexed generations of virologists: (1) the seasonal timing of respiratory illness and the rapid response of outbreaks to weather, specifically temperature; (2) the common viruses causing respiratory illness worldwide, including year‐round disease in the Tropics; (3) the rapid arrival and termination of epidemics caused by influenza and other viruses. The inadequacy of the popular explanations of seasonali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 103 publications
(231 reference statements)
0
10
0
Order By: Relevance
“…Note that influenza activity was approximated by ILI which has been proposed to be more a measure of pathogen interference that influenza activity per se. It has been suggested that respiratory viruses adapt their thermal sensitivity to local conditions, hence influenza outbreaks in the tropics [ 240 ]—implying a range of influenza variants with latitude.…”
Section: Roles For Temperature and Pollutionmentioning
confidence: 99%
“…Note that influenza activity was approximated by ILI which has been proposed to be more a measure of pathogen interference that influenza activity per se. It has been suggested that respiratory viruses adapt their thermal sensitivity to local conditions, hence influenza outbreaks in the tropics [ 240 ]—implying a range of influenza variants with latitude.…”
Section: Roles For Temperature and Pollutionmentioning
confidence: 99%
“…19,20 Differences in host body temperatures impose different thermodynamic and kinetic constraints on the structure and activity of viral proteins within cells, which is a known factor limiting inter-species virus transmission 21,22 as well as tissue tropism within a single host. 23,24 As shown in studies of extremophilic organisms, the stability and catalytic efficiency of enzymes are dependent on their thermal environments. 25,26 Proteins in organisms that regularly experience high temperatures require stronger and more extensive interactions among residues, such as disulfide bonds and salt bridges to maintain stability, 27−29 proteins in low-temperature regimes require greater internal flexibility to facilitate catalysis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We recently published a review of the factors underlying the winter seasonality and pathogenicity of respiratory viruses [1] . We showed that many respiratory viruses possess natural thermal sensitivity, meaning they replicate faster at temperatures below their hosts’ normal body temperature, confining them to the upper airways.…”
mentioning
confidence: 99%
“…Our analysis and hypothesis have important practical implications for clinical practice. For example, standing still outside and wearing insufficiently warm winter clothing are correlated with increased risk of death from respiratory illness [1] . This suggests that steps taken by individuals to avoid chilling may be protective.…”
mentioning
confidence: 99%
See 1 more Smart Citation